Accounting flexibility and managers' forecast behavior prior to seasoned equity offerings - KIM, Jae Bum (Institutional Knowledge at Singapore Management University, 2016)
This study examines the effect of accounting flexibility on managers’ forecasting behavior prior to seasoned equity offerings (SEOs). Although SEO firms have a strong incentive to convey optimistic information to boost the pre-SEO stock price, they also face enhanced litigation risk arising from SEO-related regulations. Thus, I hypothesize that managers will release positive news through their forecasts (relative to the prevailing analyst consensus) prior to an SEO only if they have the accounting flexibility to manage subsequent reported earnings to meet or exceed their forecasts. I find that managers with greater accounting flexibility are more likely to issue a forecast prior to the SEO and that their forecasts are more likely to convey positive news and are more specific. Furthermore, I find no effect of accounting flexibility for non-SEO control firms or for non-SEO periods. My results suggest that when managers experience a tension between the incentive for voluntary disclosure and high litigation risk, accounting flexibility is an important factor that determines their forecasting behavior.